Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
c) (4x - 8)[x + (-3)] = 0
=> 4(x - 2)(x - 3) = 0
=> (x - 2)(x - 3) = 0
=> x - 2 = 0 hoặc x - 3 = 0
+) x - 2 = 0 => x = 2
+) x - 3 = 0 => x = 3
Vậy x \(\in\){2;3}
11(x - 6) = 4x + 11
=> 11x - 66 = 4x + 11
=> 11x - 4x = 11 + 66
=> 7x = 77
=> x = 77/7
=> x = 11
a. ( 3x - 7 ) 5 = 32
=> 3x - 7 = 32 : 5
=> 3x - 7 = 32/5
=> 3x = 32/5 + 7
=> 3x = 67/5
=> x = 67/5 : 3
=> x = 67/5 . 1/3
=> x = 67/15
Tương tự tiếp. Chúc bạn học tốt!!!
a) ( 3x - 7 ) . 5 = 32
( 3x - 7 ) = 32 : 5
( 3x - 7 ) = 6,4
3x = 6,4 + 7
3x = 13.4
x = 13,4 : 3
x = 4,4666 ..
a, \(\frac{3}{4}x-\frac{1}{5}=\frac{7}{4}x+\frac{11}{5}\)
\(\Rightarrow\frac{3}{4}x-\frac{7}{4}x=\frac{11}{5}+\frac{1}{5}\)
\(\Rightarrow-x=\frac{12}{5}\Rightarrow x=-\frac{12}{5}\)
Vậy ...
b, \(\frac{x+1}{2}=\frac{8}{x+1}\)
\(\Rightarrow\left(x+1\right)^2=16\)
\(\Rightarrow x+1=4\)hoặc \(x+1=-4\)
\(\Rightarrow x=3\) hoặc \(x=-5\)
Vậy ..
3/4x-7/4x=1/5+11/5
(3/4-7/4).x=12/5
-1.x=12/5
x=12/5:-1
x=-12/5
vậy x=-12/5
`(x - 2)/3 = (x + 1)/4`
`(x - 2) . 4 = (x + 1) . 3`
`<=> 4x - 8 = 3x + 3`
`<=> 4x - 3x = 3 + 8`
`<=> (4 - 3)x = 11`
`=> x = 11`
`=>` `x = 11`
\(2\left(x-5\right)+3\left(2-3x\right)=5x+7\)
\(\Leftrightarrow2x-10+6-9x=5x+7\)
\(\Leftrightarrow\left(2x-9x\right)+\left(6-10\right)=5x+7\)
\(\Leftrightarrow-7x-4=5x+7\)
\(\Leftrightarrow-7x-5x=4+7\)
\(\Leftrightarrow-12x=11\)
\(\Leftrightarrow x=\frac{-11}{12}\)
\(3x-5\left(x-2\right)+7=4x-12\)
\(\Leftrightarrow3x-5x-10+7=4x-12\)
\(\Leftrightarrow\left(3x-5x\right)-\left(10-7\right)=4x-12\)
\(\Leftrightarrow-2x-3=4x-12\)
\(\Leftrightarrow-2x-4x=3-12\)
\(\Leftrightarrow-6x=-15\)
\(\Leftrightarrow x=\frac{-15}{-6}=\frac{5}{2}\)
a; -2\(x\) - 3.(\(x-17\)) = 34 - 2.( - \(x\) + 25)
- 2\(x\) - 3\(x\) + 51 = 34 + 2\(x\) - 50
2\(x\) + 2\(x\) + 3\(x\) = - 34 + 50 + 51
7\(x\) = 67
\(x\) = 67 : 7
\(x\) = \(\dfrac{67}{7}\)
Vậy \(x\) = \(\dfrac{67}{7}\)
b; 17\(x\) + 3.(- 16\(x\) - 37) = 2\(x\) + 43 - 4\(x\)
17\(x\) - 48\(x\) - 111 = 2\(x\) - 4\(x\) + 43
- 31\(x\) - 2\(x\) + 4\(x\) = 111 + 43
- \(x\) x (31 + 2 - 4) = 154
- \(x\) x (33 - 4) = 154
- \(x\) x 29 = 154
- \(x\) = 154 : (-29)
\(x\) = - \(\dfrac{154}{29}\)
Vậy \(x=-\dfrac{154}{29}\)
1)8(4x-3)-3(2-3x)=13-40x
(32x-24)-(6-9x)=13-40x
32x-24-6+9x=13-40x
41x-30=13-40x
41x+40x=13+30
81x=43
x=43/81
Vậy x=43/81
2)10x-5(1-4x)=5x-11
10x-(5-20x)=5x-11
10x-5+20x=5x-11
30x-5=5x-11
30x-5x=5-11
25x=-6
x=-6/25
Vậy x=-6/25